CFD Simulation of Two-Phase Flows in Helical Coils - Shuai Che; David Breitenmoser; David Breitenmoser; Yuriy Yu Infimovskiy; Annalisa Manera; Victor Petrov (Frontiers in Energy Research, 2020)
The behavior of two-phase flow and corresponding flow regimes in helical tubes significantly differ when compared to two-phase flows in straight tubes due to centrifugal and torsion effects. In order to gain physical insight and gather data for validating computational models, a large number of experiments were performed on a helical coil experimental setup operated with a mixture of water and air. The experimental data were used to assess the predictive capabilities of current two-phase Computational Fluid Dynamics (CFD) models based on the Volume of Fluid (VOF) approach. In the present paper, a comparison of the CFD simulation results with the high-resolution experimental data is discussed, with special emphasis on two-phase pressure drops and void fraction distributions. It is shown that the CFD VOF model is able to correctly capture the occurrence of five flow regimes observed in the experiments, namely bubbly flow, plug flow, slug flow, slug-annular flow, and annular flow. However, a good quantitative agreement for pressure drops and void fraction distributions is found in slug flow and slug-annular flow regimes only. The good agreement found only in a limited range of flow regimes demonstrates that there is not a single set of best-practice guidelines for CFD VOF models that can be applied across a wide range of two-phase flow regimes. Also, there is not a single mesh that can be used to simulate all of the flow regimes and a case-specific mesh and time-step convergence study is needed for each individual flow regime. In the current study, optimal mesh size and time step were obtained for a slug flow test case. Hence, good agreement was obtained only for similar flow regimes, leading to significant disagreement with experimental data for test cases with substantially different flow patterns.